Pro nail care : salon secrets of the professionals - Toselli, Leigh (Firefly Books, 2009)
A complete guide to the skills and tricks essential to having gorgeous nails. Step-by-step instructions to basic nail care and applying polish. Also included are sections on healthy nails and nail art.